The effect of digital marketing and product attributes on consumer purchasing decisions in sayurbox - Dwi Retno Andriani; Sahrul Dwi Riyadi; Della Aprilia Danaparamita Putri; Syera Aqila Prameswari; Gladys Oryz Berlian; Pebli Adenesli Purba; Priskilah Febi Widya Ningrum; Hermawan Syafrizal Wahyu Nurdiantoro; Soaniton David Stefanus Parlindungan (Agriekonomika, 2024)
The development of information and communication media has become one of the conveniences of accessibility experienced by every individual, supported by rampant online shopping activities. Sayurbox is a startup that sells fruit and vegetables online. Due to the closure of offline stores and the closure of partners in several areas, Sayurbox was forced to strengthen its sales strategy again, especially in the Surabaya area. The researcher's aim is to understand the purchasing decisions of Sayurbox Surabaya customers to ensure the company's business development is successful and sustainable in competition with similar start-ups in the food and beverage sector. The location of this research was determined based on the design, namely the Sayurbox branch in the Surabaya area for 2 months May - July 2023 with a sample of 100 respondents. The analytical tools used in this research consist of descriptive analysis and quantitative analysis, namely the use of the SEMP-PLS method.